Assessment of Periodontal and Hygiene Conditions of Removable Partial Dentures in Individuals with Clefts. (November 2016) - Fraga De Almeida, Ana Lúcia Pompéia; Catalani, Danilo Tomazzini; Garcia De Oliveira, Pedro César; Soares, Simone; Tunes, Fábio Sanches Magalhães; Neppelenbroek, Karin Hermana
Objective: To assess hygiene conditions in removable partial dentures (RPDs) and to compare the periodontal status between abutment and nonabutment teeth in clefts patients. Design: Cross-sectional. Settings: Tertiary referral hospital. Participants: Forty-five patients of both genders, aged 20 to 75 years, who were upper RPD wearers for at least 2 years, with cleft lip, alveolus, and/or palate who attended follow-up appointments between 2010 and 2012. Interventions: The clinical periodontal parameters assessed on abutment teeth (experimental group) and nonabutment teeth (control group) were probing depth, clinical attachment level (CAL), plaque index, and gingival index (GI). The RPDs were evaluated under the following parameters: hygiene conditions and type of clasp on abutment. Both groups were analyzed using Mann-Whitney, Kruskal-Wallis, and Dunn's statistical test. Statistical significance was set at P < .05. Results: One hundred sixty-six abutment teeth and 168 nonabutment teeth were evaluated in 45 patients. A statistically significant difference was found between the groups for the CAL parameter ( P = .03). With regard to the prostheses' hygiene conditions through the Tarbet index parameter, of the 186 quadrants evaluated, 143 scored 2 and 3. Ackers' clasps were the most frequent clasps (n = 111). A statistically significant difference was found for the GI parameter ( P = .03). Conclusions: It was possible to conclude, in this cross-sectional study, that in general terms, the use of RPDs did not interfere in the periodontal conditions of abutment teeth; however, most prostheses presented poor hygiene and high quantity of dental plaque.